A Global Blue Revolution: Aquaculture Growth Across Regions, Species, and Countries. Issue 1 (2nd January 2020) - Garlock, Taryn; Asche, Frank; Anderson, James; Bjørndal, Trond; Kumar, Ganesh; Lorenzen, Kai; Ropicki, Andrew; Smith, Martin D.; Tveterås, Ragnar
Abstract: Discussions about global aquaculture production and prospects for future growth largely focus on Asia, where most global production takes place. Countries in Asia accounted for about 89% of global production in 2016. Exclusive attention to Asian aquaculture, however, overlooks the fact that "the blue revolution" is occurring in most parts of the world. This paper examines patterns in the development of aquaculture production by analyzing growth rates across the globe at the regional, species and country levels. The results show that production in some non-Asian countries is growing more rapidly than the major Asian producers. Moreover, most developed countries have played a limited role in the blue revolution despite being leading producers as late as the 1970s.